Synthesis and biological evaluation of anti-Toxoplasma gondii activity of a novel scaffold of thiazolidinone derivatives. (1st January 2017) - Carradori, Simone; Secci, Daniela; Bizzarri, Bruna; Chimenti, Paola; De Monte, Celeste; Guglielmi, Paolo; Campestre, Cristina; Rivanera, Daniela; Bordón, Claudia; Jones-Brando, Lorraine
Abstract: We designed and synthesised novel N -substituted 1, 3-thiazolidin-4-one derivatives for the evaluation of their anti- Toxoplasma gondii efficacy. This scaffold was functionalised both at the N1-hydrazine portion with three structurally different moieties and at the lactam nitrogen with substituted benzyl groups selected on the basis of our previous structure-activity relationships studies. Using three different assay methods, the compounds were assessed in vitro to determine both the levels of efficacy against the tachyzoites of T. gondii (IC50  = 5–148 μM), as well as any evidence of cytotoxicity towards human host cells (TD50  = 68 to ≥320 μM). Results revealed that ferrocene-based thiazolidinones can possess potent anti-tachyzoite activity (TI =2–64).